Antyk w prozie J. R. R. Tolkiena - Piętka, Radosław (0302-7384, 2011)
The article tends to analyse the problems concerning the reception of classical texts and ideas in twentieth century, using as an example the prose works of J. R. R. Tolkien.
Antiquity in J. R. R. Tolkien’s prose works
Tolkien’s oeuvre and its problematic relationships with classical tradition serve in my paper as an illustration of the diverse approaches, methods, and styles of lecture concerning the nature of literary allusivity. As a point of departure in the paper has been taken the reflection on the common phrase about “antiquity in something” deployed broadly in the reception studies. T he questions raised here are as follows: what does precisely “in” mean in that metaphor? O r, to put it in more general terms, when an allusion to another text can be treated as an inherent part of interpretation? Answer to these questions was possible due to U mberto E co’s statements in the well-known dispute relating to the interpretation and overinterpretation; in conclusion I was trying to show that his criterion of textual economy in interpretation justifies somehow (as I believe) the new look on the essential T olkien’s symbol, i.e. the ring of power, as a symbol of the R oman imperial rule. This means (in the context of the translatio imperii and cultural change from pagan to Christian empire) that The Lord of the Rings can be seen in a way as a novelistic version of Augustine’s The City of God.
Keywords: John Ronald Reuel Tolkien; reception studies; literary theory; ancient tradition